2016
DOI: 10.1007/s10140-016-1399-9
|View full text |Cite
|
Sign up to set email alerts
|

Remote reading of coronary CTA exams using a tablet computer: utility for stenosis assessment and identification of coronary anomalies

Abstract: The feasibility of remote reading of coronary CT examinations on tablet computers has not been evaluated. The purpose of this study is to evaluate the accuracy of coronary CT angiography reading using an iPad compared to standard 3D workstations. Fifty coronary CT angiography exams, including a spectrum of coronary artery disease and anatomic variants, were reviewed. Coronary CT angiography exams were interpreted by two readers independently on an iPad application (Siemens Webviewer) and a clinical 3D workstat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The study cohort consisted of 50 patients with coronary CTA exams performed in the ED, selected to represent a range of CAD severity and coronary anomalies. We used the same coronary CTA cases and acquisition parameters as those in our previous study [13]. A radiology technologist anonymized and then imported the test cases from the hospital PACS into the syngo.via server (Siemens Medical Solutions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study cohort consisted of 50 patients with coronary CTA exams performed in the ED, selected to represent a range of CAD severity and coronary anomalies. We used the same coronary CTA cases and acquisition parameters as those in our previous study [13]. A radiology technologist anonymized and then imported the test cases from the hospital PACS into the syngo.via server (Siemens Medical Solutions).…”
Section: Methodsmentioning
confidence: 99%
“…Tablet computers with larger screens than the iPhone had been evaluated for the diagnosis of pulmonary embolism, and to evaluate brain CT and spinal MRI [10][11][12]. We recently demonstrated that the diagnostic accuracy of coronary CTA is comparable between the iPad and a standard workstation [13]. It is not yet established whether the iPhone is sufficient for reviewing coronary CTA exams.…”
Section: Introductionmentioning
confidence: 99%
“…However, unanimous consensus on the large-scale use of this protocol has not been reached yet, considering several disadvantages and limitations of its applicability in clinical practice [10], like the need for trained cardiac radiologists who provide 24/7 service in the ED. A possible solution to this problem could be the wide and effective diffusion of client platforms, which may enable the remote real-time consultation of CCTA images by dedicated cardiac radiologists in support to local general radiologists [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the incidence and fatality rate of coronary heart diseases in China have increased. Coronary heart disease seriously threatens the physical and psychological health ( 2 ). Thus, effective prevention and treatment of coronary heart disease is an important topic.…”
Section: Introductionmentioning
confidence: 99%